Finite difference time domain simulation of optoelectronic devices - Koustuban Ravi. (2009)
There is an increasing effort to create faster, more efficient, smaller lasers and other optoelectronic devices for various applications in communication, sensing etc. The design of devices of short dimensions with high material gain, absorption and non linearity is challenging due to myriad physical mechanisms at play in the semiconductor medium. The strongly interacting semiconductor medium is characterized by several many body effects such as dephasing, carrier-carrier scattering, carrier-phonon scattering, band gap renormalization, inter band coulomb interaction etc. The field propagation depends on refractive index of the medium which in turn depends on electric field and the other mechanisms discussed above. In the wake of such complex interplay between various phenomena, analytic theories are not sufficient for predictive design. The Finite Domain Time Difference Technique (FDTD) is a powerful and computationally expensive method which can provide a complete spatial-temporal description of various simulation parameters. Existing FDTD methods either use phenomenological expressions for gain, absorption etc or are too computationally expensive for practical device design. In this thesis we use two new models – the 4 level, 2-electron model and multi-level, multi-electron method to simulate optoelectronic devices, in particular the passively mode locked laser. The passively mode locked laser is one of the most complicated devices to simulate due to several physical phenomena such as carrier temperature dynamics, electroabsorption effects, transport, spectral hole burning, self phase modulation, dispersion effects. The presence of quantum well systems in the active media can complicate matters even further. In this thesis we present the first FDTD simulation of mode locked lasers using the 4-level, 2-electron method. Subsequently, we incorporate quantum well and electroabsorption effects and simulate a passively mode locked laser with the multi-level, multi-electron method. Parameters such as pulse width are predicted with reasonable accuracy and there are other qualitative agreements with experiment and theory alike.